2006
DOI: 10.1002/ijc.21649
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of simultaneous treatment with sodium nitrite on 2‐amino‐3‐methylimidazo[4,5‐f]quinoline‐induced rat liver, colon and Zymbal's gland carcinogenesis after initiation with diethylnitrosamine and 1,2‐dimethylhydrazine

Abstract: Combined effects of sodium nitrite (NaNO 2 ) and 2-amino-3-methylimidazo [4,5-f]quinoline (IQ) on liver, colon and Zymbal's gland carcinogenesis were assessed using a rat two-stage carcinogenesis model, with a focus on involvement of oxidative stress. Male 6-week-old F344 rats were given a single intraperitoneal injection of 200 mg/kg of diethylnitrosamine and 4 subcutaneous injections of 40 mg/kg of 1,2-dimethylhydrazine for initiation. Then, they were administered 0 or 300 ppm IQ in the diet or 0, 0.1 or 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The 8-OHdG levels of cerebral cortex were measured with a method previously described (23,24). Briefly, nuclear DNA was isolated with a DNA extractor WB kit (Wako Pure Chemical Industries, Osaka, Japan) and digested into deoxynucleotides by treatment with nuclease P1 enzyme (Yamasa Corp., Chiba, Japan) and alkaline phosphatase (Sigma-Aldrich Chemical Co., St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…The 8-OHdG levels of cerebral cortex were measured with a method previously described (23,24). Briefly, nuclear DNA was isolated with a DNA extractor WB kit (Wako Pure Chemical Industries, Osaka, Japan) and digested into deoxynucleotides by treatment with nuclease P1 enzyme (Yamasa Corp., Chiba, Japan) and alkaline phosphatase (Sigma-Aldrich Chemical Co., St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…in a DEN and DMHinitiated two-stage carcinogenesis model. (7) Body weights and food consumption were measured once a week until week 6 and thereafter once every three weeks. All surviving animals were killed under ether anesthesia at the end of week 30.…”
Section: Experimental Designmentioning
confidence: 99%
“…(5) Of several carcinogenic HCAs, none have hitherto demonstrated lung carcinogenicity in rats (6) although we recently suggested that IQ might be an exception. (7) Thus, we incidentally found that incidences of alveolar hyperplasias, adenomas and adenocarcinomas in the lung were significantly increased in a group given 300 p.p.m. IQ for 27 weeks after initiation with diethylnitrosamine (DEN) and 1,2-dimethylhydrazine (DMH), as compared with the initiation alone group.…”
mentioning
confidence: 95%
See 2 more Smart Citations